The Role of Family Functioning and Emotional Autonomy in Predicting Adolescent Depression - Pourmand, Farzaneh; Noshadi, Naser; Maredpour, Alireza (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective:  The primary objective of the present study was to investigate the role of family functioning and emotional autonomy in predicting depression among adolescents in Boyer-Ahmad County.Methods and Materials: In this descriptive-correlational study, the statistical population comprised all adolescents in Boyer-Ahmad County in 2024. A sample of 312 participants was selected using convenience sampling. Data were collected using Beck’s Depression Inventory (1996), McMaster’s Family Functioning Questionnaire (1983), and Sternberg and Silverberg’s Emotional Autonomy Scale (1986). Data were analyzed using Pearson correlation coefficient and stepwise regression.Findings: The results indicated that family functioning had a significant negative relationship with depression, and emotional autonomy also had a significant negative relationship with depression. Family functioning and emotional autonomy predicted 52% of the variance in students’ depression, with family functioning contributing more significantly to adolescent depression.Conclusion: Given the findings, the importance of addressing family functioning and emotional autonomy in depression is increasingly evident. Therefore, organizations and policy-making centers for adolescents should implement educational programs for parents and relevant authorities to enhance awareness regarding family functioning and dynamics, thereby reducing the prevalence of adolescent depression.